Photochemical synthesis of bimetallic gold/silver nanoparticles in polymer matrix with tunable absorption properties: Superior photocatalytic activity for degradation of methylene blue - Kazancioglu, Elif Ozcelik; Aydin, Meral; Arsu, Nergis (ELSEVIER SCIENCE SA, 2021)
Bimetallic nanoparticles are widely used in chemical catalysis. Their practical performance can be better exploited through morphological control by adjusting the synthetic strategy. Herein, a photochemical synthesis route was used to achieve the controlled preparation of bimetallic Au/Ag BNps. Size and shape control is achieved depending on the type of initiating radical therefore synthesized new one-component Type II photoinitiator, namely 2-thioxanthone thioacetic acid-dioxide was employed for the synthesis of Au/Ag BNp both in solution and polymer matrix. The effect of the gold/silver ratio on the nanoparticle size, shape and distribution was investigated, and the characterization of the obtained nanoparticles was performed by UV-Vis spectrophotometry, DLS and SEM techniques. Additionally, photocatalytic oxidative degradation of methylene blue was achieved with the prepared Au/Ag bimetallic nanocomposite films. By evaluating the photocatalytic oxidation degradation of methylene blue under UV-Vis light irradiation, 2:1 ratio of Au/Ag nanoparticles containing nanocomposite film exhibit the best activity compared with other composition of Au/Ag. The size and high SPR absorption band are thought to be responsible for superior photocatalytic activity.
Keywords: Gold; silver bimetallic nanoparticles; Photopolymerization; Thioxanthone-dioxide; Photocatalytic degradation; PHOTOINDUCED ELECTRON-TRANSFER; IN-SITU SYNTHESIS; SILVER NANOPARTICLES; GOLD NANOPARTICLES; PHOTOINITIATOR; AG; NANOCOMPOSITES; PLATINUM; SYSTEMS; ACID; Materials Science